Abstracts of the Scandinavian Workshop on Applied Eye Tracking (SWAET 2018) (Journal of Eye Movement Research, 2018)
This document contains the abstracts for the 2018 Scandinavian Workshop on Applied Eye Tracking (SWAET 2018) which was held at Copenhagen Business School, Denmark, 23 to 24 August, 2018..